281 Feasibility, Acceptability, and Preliminary Impact of a School-Based Sleep Promotion Program for Adolescents. (3rd May 2021) - Levenson, Jessica; Goodkind, Sara; Albert, Sara; Macuga, Bryan; Golden, Dawn; Karadus, Clay; Wehrer, Edward; Miller, Elizabeth
Abstract: Introduction: Poor sleep is common among adolescents and has been linked with school absenteeism. Though improved sleep has been associated with improved school outcomes, intervention programs for insufficient sleep are not standard in schools, few have used an individualized approach, and none have focused on youth with absenteeism. We conducted an open trial of the feasibility, acceptability, and initial impact of our school-based sleep promotion program among adolescents. Methods: Participants included 8th and 9th grade students with mild absenteeism, insufficient sleep, and sleep timing shift on the School Sleep Habits Survey (SSHS). The program included a smartphone-based sleep diary and 1-2 tailored sessions with a school staff member. Participants completed baseline and follow-up research assessments. The sleep program focused on education about sleep; cognitive strategies targeting sleep beliefs; stimulus control; and regularization of sleep and wake. We descriptively report program feasibility, acceptability, and change in sleep duration. Results: Of 33 participants approached by school staff, 12 agreed to participate and 10 completed the study. Seven participants had two program sessions and 5 participants had one program session. Sleep duration increased by 19 minutes across the entire week based on daily sleep diary, and by 31 minutes on weekdays on the SSHS. Most participants (89%) reported that the program was not a burden on their time, that the program length was just right (88%), and that they were likely to participate in research again (75%). While program feasibility was high, most youth (56%) rated program relevance as low or unknown. The most salient implementation barrier was the challenge of embedding the program into each school's existing procedures. Conclusion: A school-based sleep promotion program for adolescents with insufficient sleep and mild absenteeism is feasible, acceptable, and associated with improved sleep. An individualized approach, with sessions delivered by school staff, shows great promise for being feasible and clinically significant. Future work should focus on selecting a sample of youth with greater investment in the program to improve school attendance and implementing the program flexibly and with fidelity across schools. Support (if any): University of Pittsburgh Center for Interventions for Improve Community Health